Deskripsi Pembelajaran IPAS dalam Kurikulum Merdeka Kelas IV di SD Negeri 01 Anjongan - Izzati, Dhea Wulandari Fhara; Setyowati, Dessy; Fatmawati, Risdiana Andika (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The Independent Curriculum was introduced as a response to the need for a more flexible and relevant education to global developments. Science and Technology learning integrates scientific and social elements to provide a holistic understanding to students. This study aims to describe the implementation of Natural and Social Sciences (IPAS) learning in the Independent Curriculum in grade IV of SD Negeri 01 Anjongan. The research method used is qualitative descriptive, with direct observation as the main data collection technique. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that social science learning in grade IV of SD Negeri 01 Anjongan has been carried out well, with teachers successfully linking learning materials with daily life and practicing process skills effectively. However, challenges are still encountered in terms of providing resources and developing innovative learning methods. This research provides important insights for the development of educational practices that are more in line with the goals of the Independent Curriculum, especially in the context of basic education. It is hoped that the results of this study can be a reference for teachers and other schools in implementing science and technology learning optimally.